PP43 Feasibility and Acceptability of a Brief Intervention to Reduce Alcohol Consumption in Sexual Health Clinic Attendees. (10th September 2013) - Dimitrov, B D; Sundaram, S; Roderick, P; Frater, A; Leydon, G; Sheron, N; Dewhirst, S; Tucker, L; Maskell, J; Chatwin, J; Harindra, V
Abstract : Background: Alcohol misuse and poor sexual health are closely related Hazardous drinking is more prevalent in sexual health clinic (SHC) attendees than in the general population leading to risky sexual behaviours. Little data exists on the feasibility of integrating a Brief Intervention (BI) into the sexual health consultation. Methods: The aim was to assess the feasibility and acceptability of a brief intervention to SHC attendees. SHC attendees (≥ 16 years) were screened using the short Alcohol Use Disorders Identification Test (AUDIT) - Consumption (C) questionnaire (AUDIT-C). Males scoring ≥ 5 and females scoring ≥ 4 were randomised to either receive BI or usual care (UC) which included a standard alcohol leaflet. Clinical staff members were randomised to receive BI training. Patients saw only trained staff in BI arm and non-trained staff in UC arm. Patients completed full AUDIT questionnaire, alcohol diary and questions on sexual behaviour at baseline and follow-up. Follow-up at 6 weeks and 6 months was largely by phone interviews. A sample of consultations was audio-recorded for intervention fidelity check. Patients with AUDIT score >15 were initially excluded; this was subsequently relaxed to a score > 20. Results: Out of total 664 patients screened, 215 were eligible for randomisation and 207 were included in the final analysis - 103 (BI) and 104 (UC). Mean age was 25 years, 66% were female, most were white, nearly 50% were employed fulltime and 27% were students. Follow-up sample at 6 weeks and 6 months was 54% and 47%, respectively, being slightly higher in the UC group, although not statistically significant at either time. Both groups reduced their alcohol consumption significantly, but the total alcohol units/week fell more sharply in UC (p < 0.05). There was no significant difference in sexual behaviour between the groups though an evidence of decrease over time in the frequency of partners was seen in both groups. The fidelity check showed that BI was delivered as intended and increased consultation time by an average of 5 minutes. The staff found it acceptable and appropriate for the SHC setting. Conclusion: The brief intervention for alcohol misuse is feasible and acceptable in a SHC. The study was not powered to detect outcome differences. Screening alone was sufficient to influence drinking and sexual behaviour in both groups. Further research to optimise this intervention is needed in those drinking most heavily.